Rare bird documentation form for Pine Grosbeak at State Forest Nursery in Ames, 1986 - Munson, Eriket al (1986)
Rare bird documentation form for a Pine Grosbeak at State Forest Nursery in Ames in Story County, IA on August 24, 1986. Epson - sheet feed